Automorphic Equivalence of Multi-models Recognition - Tatjana Plotkin; Marina Knyazhansky (National Academy of Sciences of Armenia)
In this paper we provide an implementable formal algorithm for knowledge bases equivalence verification based on the formal definition of knowledge base given by B. I. Plotkin in his works and also study some important properties of automorphic equivalence of models. In addition we show that notion of automorphic equivalence is much wider than the notion of isomorphism.
Keywords: General algebraic systems